The Influence of Internal Communication and Organizational Culture on Employee Satisfaction in the Phylon Injection Section at PT Adis Dimension Footwear, Tangerang Regency - Hasan , Nieken Andini; Yulandari, Sri; Umam, Akhmad Hairul (IJOSPOL - International Journal of Social, Policy and Law, 2026)
The purpose of this study is to determine how much influence internal communication and organizational culture have on job satisfaction of employees in the Injection Phylon division at PT. Adis Dimension Footwear, Tangerang Regency. This study uses a descriptive quantitative method. The population in this study is all employees in the Injection Phylon division at PT. Adis Dimension Footwear, Tangerang Regency. The research sample amounted to 83 respondents. The results of this study indicate that partially and simultaneously, internal communication and organizational culture significantly influence job satisfaction of employees in the Injection Phylon division at PT. Adis Dimension Footwear, Tangerang Regency. Based on the results of the study, it can be concluded that the variables of internal communication and organizational culture, both partially and simultaneously, have a significant influence on job satisfaction of employees in the Injection Phylon division at PT. Adis Dimension Footwear, Tangerang Regency.